Perspectives and priorities for foreign economic activity in agri-food industry - Strashynska, Larysa; Bech, Bech (My University, 2013)
The article identifies promising directions of development of foreign trade of food products and reasonable mechanisms of regulation of foreign Agribusiness.
Keywords: agriculture; agro-industry; foreign trade; export-import transactions; foreign economic activity; аграрне виробництво; експортно-імпортні операції; зовнішня торгівля; зовнішньоекономічна діяльність; кафедра маркетингу